Combined FTIR Matrix Isolation and Ab Initio Studies of Pyruvic Acid: Proof for Existence of the Second Conformer - Reva, Igor D. (2001)
The molecular structure of pyruvic acid was investigated by matrix isolation FTIR spectroscopy, density functional theory (DFT), and ab initio calculations performed at the RHF, MP2, MP4(SDQ), and CCSD(T) levels of theory with the aug-cc-pVDZ basis set. In these calculations, the geometries of the three lowest energy conformers of pyruvic acid were fully optimized at the DFT/B3LYP/aug-cc-pVDZ and MP2/aug-cc-pVDZ levels. Additionally, the relative energies of the conformers were calculated at the MP4, CCSD, and CCSD(T) levels. Harmonic frequencies and IR intensities were then calculated for these three conformers and were used to account for the zero point vibrational energy corrections and to assist the assignment of the observed bands to the different forms. We found that two conformers are present in the Ar matrix, and both forms exhibit a planar framework with the carbonyl bonds in a trans arrangement but differ in the orientation of the hydroxyl hydrogen. By varying the temperature of the pyruvic acid vapor prior to matrix deposition we were able to separate the bands due to the two conformers and measure their enthalpy difference. The spectral signature of the second pyruvic acid conformer has been identified for the first time. Experimental enthalpy difference between the two most stable conformers was found to be 8.7(±15%) kJ mol-1, which is in good agreement with the theoretical result.